Consumo de pasto estrella africana (Cynodon plectostachyus) y Leucaena (Leucaena leucocephala) en un sistema silvopastoril (2000)
ABSTRACT: In El hatico natural reserve, located in the department of avlle del cauca, Colombia, the voluntary consumption of DM was evaluated over 1 year in a sillvipastoral system consisting of Cynodon plectostachyus / leucaena leucocephala pasture and prosopis juliflora trees. Measurements were made at 42-day intervals and split-plot desing with four replicates was used, in which the main plots corresponded to periods of the year and subplots to the type of association. Consumption of L. leucocephala was measured in a randomized complete block design in which the differences between times of the year were evaluated. In addition, the digestibility and availability of each forage vs. consumption were submitted to multiple regression analysis, and the effect of adding molasses was compared. It was concluded that silvipastoral systems similar to the one used in this study can yield an verge DM consumption of 9.5 kg/animal per day (7.7 kg of C.plectostachyus and 1.8 kg of L. leucocephala), without considering the possible consumption of P. juliflora pods during tree harvests. The maximum inclusion of L. leucocephala in the diet (29.1%) did not cause apparent toxicity problems for the animals. Voluntary forage consumption differed between periods (P<0.05), benig influenced by factors such as IVDMD, forage availability, and inclusion of molasses in the diet. Plant height of L.leucocephala and the rainy season also affected these differences. Grass consumption also differed (P<0.05) between associations, being higher in the case of l. leucocephala than in P. juliflora.